Association of Health Literacy Levels Between Family Members - Ishikawa, Hirono; Kiuchi, Takahiro (Frontiers in Public Health, 2019)
Background: Health literacy (HL) is not solely an individual skill but a distributed resource available within individual’s social networks. This study explored the associations between individual and family member HL using two separate self-report measures of HL: the European Health Literacy Survey Questionnaire (HLS-EU-Q47) and the Communicative and Critical Health Literacy scale (CCHL). Methods: A self-administered questionnaire survey was conducted with 501 pairs of Japanese residents aged 30 to 79 and their family members whom they most often consulted for help with health issues. HL was measured using HLS-EU-Q47 and CCHL. Results: The HL scores of individuals and their family members were positively correlated for both measures. The correlation was stronger for the HLS-EU-Q47, presumably because it measures the perceived manageability of health-related tasks that implicitly depend on the availability of support for an individual. In contrast, the CCHL measures a single individual’s perceived abilities. Both individual and family member CCHL scores were independently related to individual HLS-EU-Q47 scores, particularly when an individual had a family member with a higher CCHL score than his/her own. Conclusions: Limited individual ability to achieve health-related tasks might be compensated for by the higher ability of other family members. In addressing problems with limited health literacy, future studies should focus not only on the individual but also on people who can provide an individual with support.